Theoretical Aspects of Non-Monetary Employee Engagement ("Journal "U". Economy. Management. Finance.", 2017)
The article is dedicated to the review of non-monetary incentives of employee motivation, and also to the effective methods of elaboration of employee rewarding system
Keywords: motivation; non-monetary employee engagement